The morphological and morphometric study of tissues of dentoalveolar system in children with impaired course of the antenatal period. - M. S. Drogomiretskaya; Ahmad Saleh Khalyaf Salama (Medičnì Perspektivi)
Anomalies and deformation of dental system in children and adolescents contribute not only to the deterioration of dental health, bat quite often this is the cause of a wide range of somatic pathology. The aim of our study was to determine  risk factors of dental system myofunctional disorders in children with impaired course of the antenatal period using morphological and morphometric studies. The changes that have been defined in the organs examined were dystrophic and dyscirculatory and differed in degrees of severity in all parts of the oral cavity. Dystrophic changes were detected in the gums and tongue epithelium. Dyscirculatory disorders were characterized by formation of submucosal edema, development of the vascular bed hyperemia and presence of hemorrhage under the basement membrane of the epithelium and salivary gland stroma. Pronounced changes were recorded in the nerve cells of the oral cavity.